Rock Displacement at Underground Coal Gasification - V. R., Kadirov; Y. T., Nurboboev; A. A., Umirzoqov; Elbek, Muhammadiyev (Research Parks Publishing LLC, 2022)
In this article the process of underground coal gasification, its impact to the rock displacement and methods for controlling the roof stability is described.